2014
DOI: 10.1016/j.immuni.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Disorders Associated with Gain of Function of the Intracellular Sensor MDA5

Abstract: MDA5 is an essential intracellular sensor for several viruses, including picornaviruses, and elicits antiviral interferon (IFN) responses by recognizing viral dsRNAs. MDA5 has been implicated in autoimmunity. However, the mechanisms of how MDA5 contributes to autoimmunity remain unclear. Here we provide direct evidence that dysregulation of MDA5 caused autoimmune disorders. We established a mutant mouse line bearing MDA5 mutation by ENU mutagenesis, which spontaneously developed lupus-like autoimmune symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
194
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(207 citation statements)
references
References 46 publications
13
194
0
Order By: Relevance
“…Such a gain of function may confer enhanced protection against specific pathogens by driving a more rapid host innate immune response, the trade-off being enhanced susceptibility to autoinflammatory disease. Indeed, several of the patients in the study by Rice et al (2014) show clinical signs of SLE, an observation confirmed by other studies of different Mda5 polymorphisms (Cen et al, 2013;Funabiki et al, 2014). Mda5 then has a clear and interesting association with autoimmunity and provides a useful example of how different selective pressures can affect both the provision of an appropriate inflammatory response to infection and the maintenance of tissue homeostasis.…”
Section: Cytoplasmic Nucleic Acid Sensor Mutations and Diseasesupporting
confidence: 63%
“…Such a gain of function may confer enhanced protection against specific pathogens by driving a more rapid host innate immune response, the trade-off being enhanced susceptibility to autoinflammatory disease. Indeed, several of the patients in the study by Rice et al (2014) show clinical signs of SLE, an observation confirmed by other studies of different Mda5 polymorphisms (Cen et al, 2013;Funabiki et al, 2014). Mda5 then has a clear and interesting association with autoimmunity and provides a useful example of how different selective pressures can affect both the provision of an appropriate inflammatory response to infection and the maintenance of tissue homeostasis.…”
Section: Cytoplasmic Nucleic Acid Sensor Mutations and Diseasesupporting
confidence: 63%
“…Oligomerized MAVS forms a signaling complex with TRAF3, IκB kinase, and TBK1, leading to the activation of NF-κB and IRF3/7. RLR activation is controlled by several regulatory mechanisms [63-65] and aberrant activation of the MDA5-MAVS pathway can trigger autoimmune disorders [66]. …”
Section: Rna-sensing Signaling Pathwaysmentioning
confidence: 99%
“…Protective variants in IFIH1 in patients who are otherwise genetically susceptible to diabetes exhibit reduced MDA5 expression and function (12). Further, recent data have also shown that mice with elevated expression of MDA5 exhibit increased systemic autoimmune disease (13,14). However, although identification of IFN I transcriptional signatures and increased IFN I expression has implicated a role for IFN I in diabetes in mice, loss of IFN I signaling did not affect diabetes induction (15).…”
mentioning
confidence: 98%